2011
DOI: 10.15388/na.16.3.14093
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the bacterial self-organization in a circular container along the contact line as detected by bioluminescence imaging

Abstract: This paper presents a one-dimensional-in-space mathematical model of a bacterial selforganization in a circular container along the contact line as detected by quasi-one-dimensional bioluminescence imaging. The pattern formation in a luminous Escherichia coli colony was modeled by the nonlinear reaction-diffusion-chemotaxis equations in which the reaction term for the cells is a logistic (autocatalytic) growth function. By varying the input parameters the output results were analyzed with a special emphasis on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…Similar behaviour has been observed in a number of specific applications of models incorporating chemotaxis processes, such as models for tumour-macrophage interactions [21], tumour invasion [2] and host-parasitoid dynamics [23]. Furthermore, cultured Eschirichia coli bacteria populations can also exhibit highly dynamic patterning, the nature of which has been shown to be well replicated by models of the form (2): see [24,5] for details.…”
Section: Statistical Analysis a Pde Model Such Assupporting
confidence: 60%
See 1 more Smart Citation
“…Similar behaviour has been observed in a number of specific applications of models incorporating chemotaxis processes, such as models for tumour-macrophage interactions [21], tumour invasion [2] and host-parasitoid dynamics [23]. Furthermore, cultured Eschirichia coli bacteria populations can also exhibit highly dynamic patterning, the nature of which has been shown to be well replicated by models of the form (2): see [24,5] for details.…”
Section: Statistical Analysis a Pde Model Such Assupporting
confidence: 60%
“…In [22] the authors studied a specific form of chemotaxis model incorporating logistic cell growth, revealing spatio-temporal dynamics ranging from stationary patterns to periodic solutions and chaotic behaviour. Notably, this complex spatio-temporal patterning phenomenon has also been reported in cultured Eschirichia coli populations, for example see [24,5]. Examples of these various patterns are demonstrated in Figure 1; details of the chemotaxis model itself will be provided in Section 1.1.…”
mentioning
confidence: 59%
“…It has been recently shown that bioluminescence imaging can be employed to validate mathematical models of bacterial self‐organization. In particular, the abovementioned merging–emerging patterns were, to the best of our knowledge, for the first time observed experimentally in cylindrical samples of liquid cultures of bioluminescent Escherichia coli . The imagining showed luminous aggregates of bacteria merging and emerging along the three‐phase contact lines.…”
Section: Introductionmentioning
confidence: 55%
“…Optical density measurements at 600 nm (OD 600 ) were used to monitor the concentration of cells. The freshly harvested mid‐log phase cultures (OD 600 = 0.4), corresponding to the cell density of ~1.08 × 10 8 cells/mL were chosen for examination . The induction of the culture was provided by adding a stock solution IPTG into LB medium up to the final concentration of 1 mM.…”
Section: Methodsmentioning
confidence: 99%
“…Computational modeling was also applied to investigate the bacterial self-organization in small rounded containers near the three-phase contact line as detected by quasi-onedimensional bioluminescence imaging [2,40]. The spatiotemporal patterns in the fluid cultures of luminous E. coli were numerically simulated on the basis of a 1D mathematical model of chemotaxis taking into consideration the cell growth and death.…”
Section: Introductionmentioning
confidence: 99%